Efectos cardiovasculares de la contrapulsación aórtica sobre la actividad del sistema nervioso autónomo en un modelo experimental de insuficiencia cardiaca - Camus, Juan Manuel; Risk, Marcelo Raúl; de Forteza, Eduardo; Ramírez Agustín, José; Cabrera Fischer, Edmundo Ignacio (Revista Mexicana de Ingenieria Biomedica, 2005)
Intra-aortic counterpulsation is a widely used circulatory support technique in patients with heart failure refractory to pharmacological treatment. This paper presents the effects of the autonomic nervous system activity on cardiovascular function during conventional intraaortic counterpulsation in an animal model of acute heart failure. Recordings of 6 minutes of electrocardiographic, aortic pressure and pulmonary arterial flow signals were stored before and during mechanical circulatory assistance, before and after heart failure induction by a high dose of halothane. Heart rate, mean aortic pressure, mean pulmonary flow variability and baroreflex sensitivity were analyzed off-line, in both time and frequency domain. Non significant differences were caused by mechanical assistance by the intra-aortic counterpulsation, this lack of changes suggest that this technique is able to improve the hemodynamic changes induced by heart failure in sheep, without significant changes in aortic pressure and heart rate variability and baroreflex control.